One Method to Improve the Official Poverty Line in Indonesia - Carunia Mulya Firdausy (Journal of Indonesian Social Sciences and Humanities, 2016)
Poverty is one of the long standing problems in Indonesia. Using the national absolute poverty line, it was estimated that the proportion of the poor has declined from 40.1% in 1976 to 10.5% in 2014. However,many people claim that the above percentage of the poor is only true in terms of statistics. The poor argue that the amount of rupiah expenditure set as the ofcial poverty line is inadequate to fulfl their basic needs. This paper, based on a feld survey of 360 respondents of the poor and the non-poor in three villages in three different provinces located in the Eastern, Western and Central parts of Indonesia, aims at examining a method to improve the national poverty line and to determine the minimum rupiah expenditure of the poverty line using a subjective approach. The method used to examine this research question is by - using questionnaires, Focus Group Discussion (FGD) and in depth interviews. Sample respondents were asked their perceptions on variables, dimensions and indicators that should be accommodated in formulating the subjective poverty line. They were also questioned about the minimum rupiah expenditure threshold to defne the subjective poverty line. The study found that the ofcial poverty line that has been determined by the government was far below the subjective poverty line that was defned by the respondents. Also, the variables, dimension and indicators that should be accommodated in the national poverty line should not only be food items, but also access to employment, housing, health and education for children. The minimum rupiah expenditure of the poverty line was argued to be more than Rp 500 000 equal to US$40 per capita per month. This minimum rupiah expenditure of the subjective poverty line is almost double that of the ofcial poverty line set at the average ofRp 300 000 or US$24 per capita per month. Therefore, the government not only needs to revise the present poverty line, but also needs to revise policies and programs to eliminate poverty by taking into account the dimension and variables of poverty viewed by the poor and the non-poor. If not, the incidence of poverty will remain with us.